Pre-Islamic Monotheism in Arabia - Gibb, Hamilton A. R. (Harvard theological review, 1962)
The search for the presumed “sources” of Muhammad's religious ideas, as these are expressed in the Qur'an, has inspired a considerablerange of studies, varying in tone from tentative to polemical. Most writers on the topic seek to demonstrate either a predominantly Jewish or a predominantly Christian “influence.” It is relatively easy, of course, to compile a catena of passages from the Qur'an which can be paralleled by Scriptural texts or by haggadic or apocryphal materials or compared with the practices of Jewish or Christian communities. The argument tends to become inconclusive on the whole; Jewish scholars who argue for a Jewish source or sources are apt to forgetthat the Old Testament was as much a part of Christian as of Jewish Scripture and that even haggadic supplements had long since been taken up into Christian writings; Christian scholars who argue for a Christian source or sources are somewhat embarrassed by Muhammad's decisive rejection of Christological doctrine;and each side can produce valid arguments against the other.